IMPLEMENTATION OF SMALL HYDROPOWER PLANTS IN AGRICULTURE - Topvoldiyev Nodirbek Abdulhamid o`g`li; Shavkatbekov Husanbor Azamjon o`g`li (Лучшие интеллектуальные исследования, 2024)
Abstract. In this article, the guidelines for the application of small hydropower plants to agriculture were considered.